Novel Inflammatory Prognostic Markers in Lung Cancer Patients Treated with Definitive Chemoradiotherapy - Hakan Harputluoglu; Alper Yeniçeri; Ahmet Gulmez (Genel Tıp Dergisi)
Primary lung cancer is the most common cancer worldwide and is an increasingly common problem. The primary endpoint of this study was; to investigate the effect of radiotherapy dose and neutrophil-lymphocyte ratio (NLR) on overall survival (OS) and progression-free survival (PFS). We retrospectively examined 99 patients who were stage III A and stage III B at the time of diagnosis, who did not receive surgical treatment, and who received definitive chemoradiotherapy. Data of patients such as sex, age, ECOG status, tumor location, pathological subtype, radiotherapy dose, type of chemotherapy, neutrophil/lymphocyte ratio (NLR), and some biochemical parameters and PFS and OS were included in the study by scanning the patient's files. The radiotherapy cut-off value was accepted as 60 Gray. OS was statistically better in patients who received radiotherapy at doses of 60 Gray and above. When the patients with radiotherapy dose less than 60 Gy and patients with more than 60 Gray were evaluated in two groups, the overall survival was 8,569 ± 1,404 / month and 14,326 ± 1,209 / month, respectively. (p <0.05). When we evaluate the patients based on NLR; It was observed that the overall survival of patients below NLR 4 at the time of diagnosis was statistically significantly better. The overall survival of patients with NLR <4.0 and NLR> 4 was 14.32 ± 1.30 / month and 10.54 ± 1.16 / month, respectively. (p <0.05)